Evolution of the valence state of Ru metal ions in correlation with the structural and electronic properties of double perovskite ruthenates; A2SmRuO6 (where A = Ba & Sr). Issue 12 (9th March 2023) - Dani, Sahil; Pandit, Rabia; Sharma, Hitesh; Arya, A.; Choudhary, R. J.; Goyal, Navdeep; Singh, Jarnail; Kumar, Rakesh
Abstract : This novel study is crucial in understanding the intriguing electronic, structural and chemical properties of special double perovskite compounds, Ba2 SmRuO6 and Sr2 SmRuO6, for their applications as "Spintronics based devices". Abstract : We report combined experimental and theoretical investigations on the oxidation states of Ru ions in the double perovskite ruthenates: Ba2 SmRuO6 (BSRO) and Sr2 SmRuO6 (SSRO). The Rietveld analysis of the X-ray diffraction (XRD) patterns confirms the formation of a single-phase cubic structure (space group- Fm 3̄ m ) for BSRO and a monoclinic structure (space group- P 21 / n ) for SSRO compounds. FTIR and Raman spectra measured at room temperature comply with the structural symmetry obtained from their X-ray diffraction data. The detailed analyses of the magnetization data suggest that Ru ions in these compounds are present in mixed oxidation states as Ru 4+ and Ru 5+ . The oxidation state of Ru ions has been investigated from analyses of their X-ray photoemission spectroscopy (XPS) data, and was further re-confirmed from analyses of their M2, 3 edge X-ray Absorption Spectroscopy (XAS) spectra. XAS spectra on comparison with that of RuO2 (RO) indicate that Ru ions in these ruthenates are present in an oxidation state greater than +4. For further insights into the experimental data, core-level spectroscopy calculations were carried out within DFT using CASTEP software to compute the M2, 3 edges. Interestingly, the BSRO and SSRO compounds have been found to exhibit semiconducting behavior having band gaps of 1.1 eV and 1.18 eV, respectively, from the DFT+ U calculations. The calculated Ru-M2, 3 edge spectra are found to be in good agreement with our experimental XAS spectra, indicating the possibility of a mixed oxidation state of Ru ions (+4 or +5) in SSRO and +5 oxidation state for Ru ions in the BSRO compound. The observed signatures of Jahn–Teller (J–T) distortions from the XAS study for the SSRO compound are also in line with the monoclinic structure as obtained from the analysis of their XRD data. The present findings are crucial in understanding the intriguing electronic, structural and chemical properties of the as-proposed double perovskite compounds and their applications as "Spintronics devices".